Influence of Sense of Belonging to a School on Learners’ Loneliness in Single Gender and Co-Educational Institutions in Murang’a County, Kenya - Peter Muriuki Baru; Lucy Ndegwa; Johannes Njagi Njoka; Zakaria Mbugua (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The influence of the sense of belonging to school on learners’ loneliness in single gender and co-educational schools in the world and Kenya in particular is not clearly known and documented. Available literature indicates that the learners’ sense of belonging to school significantly impacts on their loneliness. The purpose of this study was to examine the influence of the sense of belonging to school on learners’ loneliness in single gender and co-educational schools in Murang’a County in Kenya. The study was guided by the following specific objectives, which were to; Compare the levels of loneliness among learners in single gender and co-educational schools in Murang’a County and assess power of sense of belonging to school in determining the loneliness levels among learners in single gender and co-educational schools in Murang’a County.  The study adopted the cross-sectional survey research design. The Krejecie & Morgan Table was used to select a sample of 435 participants from a target population of 12,400 form two learners from single gender and co-educational secondary schools in the County.  Data was collected using two standardized measurement instruments; the Perth aloneness-loneliness scale (PALs) while sense of belonging to school was measured using five statements in a five point Likert scale developed for the study. Administration of the questionnaire was done during normal school days by trained research assistants.  Data was analysed using the descriptive and inferential statistics with the aid of the Statistical Package for Social sciences (SPSS) version 20.0. The findings of the study indicated that low sense of belonging to school for girls in co-educational institutions was correlated to high levels of loneliness. From the findings of the study, it is concluded that there is need to strengthen the psychosocial support systems for learners in co-educational schools through mentorship, guidance, coaching and counselling to facilitate appropriate adjustments of the learners in the schools so as to promote their learning outcomes.